SOSIALISASI DAN PELATIHAN TEKNOLOGI OZONISASI UNTUK MENINGKATKAN PRODUKSI BENIH IKAN PADA UNIT PEMBENIHAN RAKYAT KARYA YUDA - Dian Puspitasari; Intan Zahar; Tri Andriani; Riska Hariyani; Rumiati Rumiati; Aisyah Alfaresa (Smart Education, 2026)
Abstract: Aquaculture has significant potential to contribute to local economic development. However, one of the major challenges faced by fish farmers is that fish fry production remains below target, with productivity below 70%. This low level of production negatively affects farmers' income and the sustainability of their aquaculture operations. One of the hatcheries facing this challenge is the Unit Pembenihan Rakyat Karya Yuda. The application of ozonation technology offers a promising approach to improving water quality and enhancing fish fry production. However, knowledge of how to apply ozonation technology remains limited among fish farmers. This community service program aimed to enhance fish farmers' knowledge and understanding of ozonation technology and its application in aquaculture. The program consisted of three stages: preparation, implementation, and evaluation. The results showed that applying ozone gas to pond water improved catfish fry productivity. The water quality parameters remained within the normal range, with a temperature of 30.2°C, a pH of 7.9, and a dissolved oxygen (DO) concentration of 6.7 mg/L. In addition, the fish egg hatching rate exceeded 85%, the fish fry exhibited faster growth, and no fungal infection was observed on the fish eggs. In conclusion, this community service program demonstrated that the application of ozonation technology benefited UPR Karya Yuda by maintaining good water quality and increasing fish fry production. Keyword: fish; ozone plasma; pond Abstrak: Budidaya perikanan memiliki potensi yang besar dalam mendorong peningkatan perekonomian di masyarakat. Kendala yang dihadapi oleh pembudidaya ikan diantaranya produktivitas benih ikan yang masih dibawah target yaitu < 70%. Produksi ikan yang rendah akan berpengaruh terhadap pendapatan pembudidaya ikan. Pembudidaya ikan yang mengalami masalah seperti ini contohnya Unit Pembenihan Rakyat Karya Yuda. Solusi yang dapat dipilih yaitu penggunaan teknologi ozonisasi. Akan tetapi, informasi terkait manfaat teknologi ozonisasi ini masih minim di kalangan pembudidaya ikan. Tujuan kegiatan pengabdian kepada masyarakat yaitu meningkatkan pengetahuan dan informasi kepada pembudidaya ikan terkait teknologi ozonisasi.. Hasil kegiatan yaitu gas ozon yang diaplikasikan pada air kolam mendukung produktivitas benih ikan lele. Parameter kualitas air tergolong normal yaitu suhu sebesar 30,2 0C, nilai pH.nya 7,9 dan nilai DO yaitu 6,7 mg/L. Sedangkan daya tetas telur ikan > 85%, pertumbuhan benih ikan lebih cepat dan tidak ditemukan jamur pada telur ikan. Simpulan dari kegiatan pengabdian kepada masyarakat adalah teknologi ozonisasi memberikan manfaat untuk UPR Karya Yuda, yaitu mempertahankan kualitas air tetap baik bagi ikan serta meningkatkan produksi benih ikan. Kata kunci: ikan; plasma ozon; kolam